Adrenal Insufficiency after Long-term use of Topical Glucocorticoids in Patients with Advanced Cutaneous T-cell Lymphomas: A Case Series - Valerie Glutsch; Patrick Schummer; Ann-Cathrin Koschker; Matthias Goebeler; Marion Wobser (Medical Journals Sweden, 2024)
Abstract is missing (Short communication)